ANALYZING ISLAMIC BANKS STABILITY: EVIDENCE FROM SOUTHEAST ASIA AND THE GULF COOPERATION COUNCIL COUNTRIES (GCC) - Rani, Lina Nugraha; Bt Mohd Ariffin, Noraini; Ratnasari, Ririn Tri; Aulia, Melananda Risky (Universitas Airlangga, 2024)
Introduction: This study investigates the factors, particularly those related to banks and macroeconomics, that influence the stability of 38 Islamic banks in Southeast Asian countries and the Gulf Cooperation Council (GCC) based on annual data from 2013 to 2020. The study aims to identify key determinants of stability across distinct regions and highlight the significance of these determinants in maintaining financial stability in Islamic banks. Methods: Using a quantitative approach with panel regression analysis, this study examines various factors influencing Islamic bank stability in Indonesia, Malaysia, the United Arab Emirates, and Qatar. Specific factors considered include Assets, Non-Performing Financing (NPF), Gross Domestic Product (GDP), and Return on Assets (ROA). Results: The findings reveal that in Indonesia, Assets, NPF, and GDP are significant factors influencing bank stability. In Malaysia, ROA, Assets, and GDP are significant, whereas in the United Arab Emirates, only ROA is significant, and in Qatar, only Assets are significant. Conclusion and suggestion: Islamic banks should pay attention to the Z-Score from previous periods and manage assets and liabilities effectively to ensure stability. Effective macroprudential supervision is also necessary to enhance resilience in the financial system. Maintaining asset quality is essential for mitigating risks to banking stability.